Sustainable and eco-friendly synthesis of biodiesel from novel and non-edible seed oil of Monotheca buxifolia using green nano-catalyst of calcium oxide. (January 2022) - Rozina; Ahmad, Mushtaq; Elnaggar, Ashraf Y.; Keat Teong, Lee; Sultana, Shazia; Zafar, Muhammad; Munir, Mamoona; Hussein, Enas E.; Zain Ul Abidin, Sheikh
Graphical abstract: Highlights: Efficient conversion of low cost feedstock of Monotheca buxifolia into Biodiesel with 95% yield. Catalytic application of recyclable green nano-particles of CaO in transesterification. Central Composite Design for optimization reactions of transesterification using RSM. Application of innovative analytical techniques for characterization of catalyst and methyl ester. Fuel properties of biodiesel were found equivalent to international standards of fuel. Abstract: Presently, biodiesel offers a sustainable and renewable substitute for exhausting fossil fuels such as Petro-diesel. Large scale production of biodiesel could lead to positive outcomes in terms of environmental quality by reducing greenhouse gasses emission and Societal-Economic development. Hence, this research work focused on biodiesel synthesis from novel and non-edible seed oil of Monotheca buxifolia using green nano-particles of calcium oxide synthesized with aqueous leaves extract of Boerhavia procumbens . Advanced techniques like X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Energy diffraction X-Ray (EDX) were used to characterize calcium oxide nano-particles. High yield of biodiesel (95%) was obtained at optimum reaction conditions such as methanol to oil molar ratio of 9:1, catalyst loading 0.83 (wt.%), reaction time 180 min and temperature 85 °C. Gas Chromatography/Mass spectroscopy (GC/MS) analysis of biodiesel revealed four distinct peaks of methyl esters. Results of Fourier-transform infrared spectroscopy (FTIR) and Nuclear magnetic resonance (NMR) confirmed the formation of methyl esters in biodiesel sample. Fuel properties of biodiesel such as density (0.821 kg/m 3 ), viscosity (5.35 mm 2 /s), cloud point (-8 ◦C), pour point (-9 ◦C) and flash point (95 ◦C) were found equivalent to international ASTM D-6571, EN 14, 214 and China GB/T 20828–2007 standards. It was finally concluded that Monotheca buxifolia is a highly potential, eco-friendly, and cheaper biomass feedstock for biodiesel production.